Freudian mythologies Greek tragedy and modern identities - Bowlby, Rachel 1957- (Oxford Oxford University Press, 2010)
Rachel Bowlby suggests that, with the multiplication of sexual roles, family forms, and reproductive technologies, Freud's 'Oedipus complex' may have lost its relevance. This book takes two Freudian routes to think about some of the entanglements of identity.
Electronic reproduction.
Keywords: Oedipus complex; Electra complex; Psychoanalysis -- Greek influences; Greek drama (Tragedy) -- History and criticism